Microplastic contamination and removal efficiency in greywater treatment using a membrane bioreactor - Ittisupornrat, Suda; Namyuang, Chayanin; Phetrak, Athit; Sriromreun, Paranee; Theepharaksapan, Suthida (Frontiers in Microbiology, 2025)
Microplastic (MP) contamination in aquatic environments is a critical concern due to its potential effects on aquatic ecosystems. MP contamination is often unsatisfactorily eliminated using conventional wastewater treatment systems. Membrane bioreactor (MBR) is a modern solution for wastewater treatment offering significant advantages over traditional activated sludge systems, such as a smaller footprint and the ability to produce high-quality effluent. In this study, a pilot-scale MBR was conducted to evaluate MP removal from real greywater. The overall treatment performance for MP removal reached up to 90%, with the MP concentration in the permeate effluent being 0.02 MP L−1. The major MP size distribution was 101–300 μm, with polypropylene as the predominant MP type. Remarkably, polyester fibers were highly predominant in the suspended sludge. Furthermore, Alphaproteobacteria, Bacteroidetes, and Actinobacteria were the predominant communities in the MBR sludge, which preferably formed a biofilm associated with MP accumulation. This study underscores the potential of MBR technology for efficient MP removal in household buildings, contributing to the mitigation of MP discharge into the environment. Implementing MBR systems is a crucial step toward safeguarding aquatic ecosystems and preserving environmental integrity with respect to the corresponding increase in MP pollution.